Japan’s flashback to traditional capitalism - Kwon, Jaok (Global economic elites and the new spirit of capitalism, 2024)
This chapter presents compelling evidence that challenges the notion of Japan aligning with neoliberal management thinking, thereby questioning the existence of a global management elite. Through life-course analysis, it is observed that there is a minimal representation of managers with academic backgrounds in economics or business administration in Japan. The data further underscores a limited degree of internationalization in Japanese managers’ education, though international working experience has gained significance. Examining neoliberal mindsets reveals that Japanese top managers are not gravitating towards neoliberalism in financial market orientation, leadership principles, or life conduct. The financial market orientation mindset, influenced by the 2008 financial crisis in the USA and the failure of shareholder maximization principles, demonstrates a strong inclination to revert to traditional Japanese capitalism. Leadership values continue to emphasize relationships, harmony, and coordination among company members, supported by the dominance of internal labor market promotions. Leaders from this internal market are expected to foster stable relationships based on long-term commitment and loyalty. In terms of life conduct, neoliberal ideas are also rebuffed, despite a changing mindset among young managers regarding family. Family is still perceived as a factor to be minimized for professional success, rather than being a driving force or tool for optimizing work performance.